An Empirical Analysis of a Skill-Based Pay Program and Plant Performance Outcomes - Murray, Brian; Gerhart, Barry (Academy of Management Journal, 1998)
Despite the documented increase in skill-based pay programs in organizations, little evidence exists on whether these plans achieve the results intended. Using time series data, this study examined productivity and labor cost outcomes over 37 months. Likewise, quality outcomes were examined using time series data from treatment and comparison facilities. The results indicated greater productivity (58%), lower labor cost per part (16%), and favorable quality outcomes (82 percent scrap reduction vis-à-vis the comparison facility) with skill-based pay. These results are consistent with the behavioral and operations theories underlying skill-based pay.